Relationship between airborne pollen and skin prick test results in Elazig, Turkey - Kilic, M.; Altunoglu, M. K.; Akpinar, S.; Akdogan, G. E.; Taskin, E. (Springer, 2019)
This study investigated the relationship between the types of pollen in the air and sensitization to pollen in a skin prick test in allergic children. The pollen in the atmosphere of Elazig city was measured between June 2013 and June 2014. The study included 520 children with allergic complaints. In the atmosphere of Elazig city, pollen belonging to a total of 38 taxa was identified, including 20 woody plants and 18 herbaceous plants. The annual pollen integral of 108,313 pollen day/m(3) from the 38 taxa was identified. The most common pollen detected was woody plants (76.4%), weeds (14.1%), Poaceae (Gramineae) (9.1%), and unidentified plants (0.4%). The skin prick test in allergic children found that they were most commonly sensitized to mixture of grasses and cereals (43.8%), weed (14.1%), tree mixture I (10.1%), and tree mixture II (7.9%). There was no direct relationship between the frequency of pollen types in the atmosphere and the sensitization frequency to pollen, as identified by the skin prick test in allergic patients. We believe that the data from this study will provide new information to other researchers and clinicians in the evaluation of allergic diseases.
Keywords: Airborne pollen; Volumetric method; Allergic children; Skin prick test